2013
DOI: 10.1039/c2cs35301f
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of ordered mesoporous carbons

Abstract: Ordered mesoporous carbon materials have recently aroused great research interest because of their widespread applications in many areas such as adsorbents, catalysts and supports, gas storage hosts, and electrode materials. The direct synthesis strategy from organic-organic self-assembly involving the combination of polymerizable precursors and block copolymer templates is expected to be more flexible in preparing mesoporous carbons, compared with the traditional nanocasting strategy of complicated and high-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
380
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 551 publications
(386 citation statements)
references
References 232 publications
(343 reference statements)
3
380
0
3
Order By: Relevance
“…Zhou et al [92] reported the preparation of wet carbon from corncob with tailored pore sizes using a KOH activation agent. The wet carbon had an optimum narrow pore size distribution from 1.6 to 2.8 nm and presented a very high CH 4 storage capacity of 65 wt% at 275 K and 33.5 bar.…”
Section: Ch 4 Storage Technology Using Porous Adsorbentsmentioning
confidence: 99%
“…Zhou et al [92] reported the preparation of wet carbon from corncob with tailored pore sizes using a KOH activation agent. The wet carbon had an optimum narrow pore size distribution from 1.6 to 2.8 nm and presented a very high CH 4 storage capacity of 65 wt% at 275 K and 33.5 bar.…”
Section: Ch 4 Storage Technology Using Porous Adsorbentsmentioning
confidence: 99%
“…Generally, OMC can be synthesized using low-molecular-weight resol as carbon source, silica as an additive and triblock copolymer Pluronic F127 as a structure-directing agent via the evaporation-induced self-assembly (EISA) method (Ma et al, 2013;Li and Zhao, 2013). Benefiting from its relatively large surface area and pore volume, OMC shows great potential advantages as an adsorbent in environmental remediation processes.…”
Section: Introductionmentioning
confidence: 99%
“…1 The interest for these kinds materials is mainly due to the fact that they generally are low cost, environmentally friendly, and available in large scale since they are recovered from natural sources. In this context, nanoporous minerals such as zeolite, bentonite, and montmorillonite 2,3 have shown good promise to replace the commonly used mesoporous materials.…”
Section: ■ Introductionmentioning
confidence: 99%